Gas phase dicyanoacetylene (C4N2) on Titan: New experimental and theoretical spectroscopy results applied to Cassini CIRS data - Jolly, A; Cottini, V; Fayt, A; Manceron, L; Kwabia-Tchana, F; Benilan, Y; Guillemin, J; Nixon, C; Irwin, P (Academic Press Inc., 2015)
Dicyanoacetylene has not been observed so far in the gas phase in Titan's atmosphere but this molecule is still on the list of the detected species, on the basis of the correspondence between a solid phase feature measured at 478cm-1 in the laboratory and a spectral feature observed by Voyager. In this work, the infrared spectrum of gaseous C4N2 has been investigated to improve our knowledge of the band intensities and the line parameters for this molecule. Results of previously investigated bands have been revised and the intensity of the ν9 band at 107cm-1, measured for the first time, was found to be the strongest absorption in the whole infrared domain. We have also improved the analysis of the complex rotational and hot band structure of C4N2 in order to obtain the first line lists for both bending modes ν8 and ν9. Using our radiative transfer code including the new line list of the strong ν9 band, we have searched for the signature of C4N2 at 107cm-1 in the atmosphere of Titan utilizing Titan CIRS far infrared spectra. Despite averaging a large number of CIRS spectra at northern latitudes during the very favorable Titan winter, no gaseous C4N2 could be detected. At the 1-σ level we obtain an abundance upper limit of 5.3×10-10 for the limb average which is lower than or comparable to previously inferred values. As a consequence, the absence or very low amount of gaseous C4N2 makes quite puzzling its presence in the solid phase with an abundance compatible with the observed spectral feature at 478cm-1.